Manipulation of number of players and bouts duration in small-sided games in youth soccer players - Alcantara, C. H.; Teixeira, A. S.; Teixeira, R. M.; Dutra, G. O.; Nakamura, F. Y.; Castagna, C.; da Silva, J. F. (Sport Sciences for Health, 2021)
Purpose To examine the influence of player number, bout duration and their interaction on small-sided game (SSG) variations in running performance, perceptual response and technical components in under-14 soccer players.